Non-Violent Communication in everyday life - Aktar, Afrin; Goon, Swmaranika; Pal, Ujjal; Zaman, Thahina (2021)
In March, members of the team in Bangladesh (Community Mobilisers and Lead Community Mobilisers) participated in a training course in non-vi olent communication (NVC). NVC is a communication technique that prior itises listening over speaking. It aims to improve communication by ac hieving a deeper understanding of our emotions and values and what we observe in the behaviour of others. The training was facilitated by Pa ul Kahawatte, a UK-based mediator, facilitator and trainer, Roufun Nah er, a lecturer at the University of Dhaka and NVC practitioner in Bang ladesh, Neil Howard, co-lead of Social Protection for CLARISSA and Jin iya Afroze, CLARISSA Country Coordinator in Bangladesh. The aim of the training was to support the community mobilisers to explore and pract ice different ways of communicating and facilitating. This will help t hem support communities to come together and build their collective po wer for the social protection ‘cash plus’ pilot. Lemon Roy, a communit y mobiliser was grateful for the experience; “I had little knowledge a bout Non-Violent Communication before participating in the training. I didn’t know that passive listening and the communication gap between two people could lead to conflict. I have learned about tools and tech niques in conflict mediation and the importance of understanding the f eelings and needs of other people.”.